Default-mode network changes in Huntington's disease: an integrated MRI study of functional connectivity and morphometry. - Mario Quarantelli (Public Library of Science (PLoS), 2013)
Previous MRI studies of functional connectivity in pre-symptomatic mutation carriers of Huntington's disease (HD) have shown dysfunction of the Default-Mode Network (DMN). No data however are currently available on the DMN alterations in the symptomatic stages of the disease, which are characterized by cortical atrophy involving several DMN nodes. We assessed DMN integrity and its possible correlations with motor and cognitive symptoms in 26 symptomatic HD patients as compared to 22 normal volunteers, by analyzing resting state functional MRI data, using the Precuneal Cortex/Posterior Cingulate Cortices (PC/PCC) as seed, controlling at voxel level for the effect of atrophy by co-varying for gray matter volume. Direct correlation with PC/PCC was decreased, without correlation with atrophy, in the ventral medial prefrontal cortex (including anterior cingulate and subgenual cortex), right dorso-medial prefrontal cortex, and in the right inferior parietal cortex (mainly involving the angular gyrus). Negative correlations with PC/PCC were decreased bilaterally in the inferior parietal cortices, while a cluster in the right middle occipital gyrus presented increased correlation with PC/PCC. DMN changes in the ventral medial prefrontal cortex significantly correlated with the performance at the Stroop test (p = .0002). Widespread DMN changes, not correlating with the atrophy of the involved nodes, are present in symptomatic HD patients, and correlate with cognitive disturbances.